2021
DOI: 10.5114/aoms.2019.85449
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ki67 and myogenic regulatory factor expression by tocotrienol-rich fraction ameliorates myogenic program of senescent human myoblasts

Abstract: IntroductionReplicative senescence results in dysregulation of cell proliferation and differentiation, which plays a role in the regenerative defects observed during age-related muscle atrophy. Vitamin E is a well-known antioxidant, which potentially ameliorates a wide range of age-related manifestations. The aim of this study was to determine the effects of tocotrienol-rich fraction (TRF) in modulating the expression of proliferation- and differentiation-associated proteins in senescent human myoblasts during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Strikingly, hsa circ 0076931 overexpression dramatically reduced mean tumor volume and weight. Ki67 is a nuclear protein used as a cell proliferation marker in human tumors [29]. We found that hsa circ 0076931 dramatically decreased the percentage of Ki67-positive cells.…”
Section: Discussionmentioning
confidence: 73%
“…Strikingly, hsa circ 0076931 overexpression dramatically reduced mean tumor volume and weight. Ki67 is a nuclear protein used as a cell proliferation marker in human tumors [29]. We found that hsa circ 0076931 dramatically decreased the percentage of Ki67-positive cells.…”
Section: Discussionmentioning
confidence: 73%
“…Sarcopenia is a common syndrome in the elderly and patients with chronic diseases [8,14] . The quantity of skeletal muscle is speculated to be linked to the prognosis of patients with tumors through various mechanisms including increased proinflammatory cytokines, decreased levels of myokines and growth factors [9,[25][26][27] . In this study, we indicated that preoperative FFMI is a potential biomarker for overall survival in patients with MICC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tocotrienol stock solution preparation varies across the studies. Our group and other research teams employed overnight serum incubation, where serum contains albumin and transfer proteins that could enhance the cellular uptake of tocotrienol, which is highly lipophilic [29,31,[99][100][101][102][103][104][105][106]. Similarly, the use of bovine serum albumin in dissolving tocotrienol also improved its cellular uptake [43,49,107].…”
Section: Limitationsmentioning
confidence: 99%